The ultrastructure of a stria vascularis in the auditory organ of the cuban crocodile (Crocodylus rhombifer) - Li, Hao; Staxäng, Karin; Hodik, Monika; Melkersson, Karl-Gunnar; Rask-Andersen, Helge (Frontiers in Cell and Developmental Biology, 2023)
Background: An endocochlear potential (EP) exists in the mammalian cochlea generated by the stria vascularis and an associated fibrocyte network. It plays an essential role for sensory cell function and hearing sensitivity. In nonmammalian ectothermic animals the EP is low and its origin somewhat unclear. In this study, we explored the crocodilian auditory organ and describe the fine structure of a stria vascularis epithelium that has not been verified in birds. Material and Methods: Three Cuban crocodiles (Crocodylus rhombifer) were analyzed with light and transmission electron microscopy. The ears were fixed in formaldehyde or glutaraldehyde. The temporal bones were drilled out and decalcified. The ears were dehydrated, and embedded and was followed by semi-thin and thin sectioning. Results: The fine structure of the crocodile auditory organ including the papilla basilaris and endolymph system was outlined. The upper roof of the endolymph compartment was specialized into a Reissner membrane and tegmentum vasculosum. At the lateral limbus an organized, multilayered, vascularized epithelium or stria vascularis was identified. Discussion: Electron microscopy demonstrates that the auditory organ in Crocodylus rhombifer, unlike in birds, contains a stria vascularis epithelium separate from the tegmentum vasculosum. It is believed to secrete endolymph and to generate a low grade EP. It may regulate endolymph composition and optimize hearing sensitivity alongside the tegmentum vasculosum. It could represent a parallel evolution essential for the adaptation of crocodiles to their diverse habitats.